Selection of the extremes - male junior and adult ice hockey success in relation to relative age and its interaction with biological maturation - Niklasson, E.; Rietz, M.; Lindholm, O.; Lind, J.; Johnson, D. M.; Lundberg, T. R. (Sports Medicine - Open, 2025)
Objectives This study aimed to investigate the relationship between the relative age effect (RAE) and success in ice hockey during adolescence and adulthood in male Swedish players, as well as potential interactions between relative age (RA) and biological maturation.